Bilingualism as a Contributor to Cognitive Reserve? Evidence from Cerebral Glucose Metabolism in Mild Cognitive Impairment and Alzheimer’s Disease - Kowoll, Magdalena Eva; Degen, Christina; Gorenc, Lina; Küntzelmann, Anika; Fellhauer, Iven; Giesel, Frederik; Haberkorn, Uwe; Schröder, Johannes (Frontiers in Psychiatry, 2016)
Objective: Bilingualism is discussed as one factor contributing to ‘cognitive reserve’ (CR) as it enhances executive control functions. To elucidate the underlying cerebral correlates regional glucose uptake was compared between bilinguals and monolinguals with mild cognitive impairment (MCI) and beginning Alzheimer´s disease (AD) by using [18F]fluorodeoxyglucose (FDG) positron emission tomography (PET). Methods: 30 patients (73.2 ± 7.4) diagnosed with MCI or probable AD received physical and neuropsychological examinations, blood tests and FDG-PET scans. 16 patients were classified as lifelong bilinguals following the criterion of Bialystok et al.; groups were matched for age, sex and MMSE scores. Analyses were conducted using SPM 8 using the whole brain as reference region for intensity normalization controlling for years of education. Results: Bilingual patient groups showed substantially greater impairment of glucose uptake in frontotemporal and parietal regions (including Brodmann areas 9, 47, 40 and 21) and in the left cerebellum relative to monolingual patients. Conclusions: Bilingualism is likely to contribute to CR given that bilingual patients showed more severe brain changes than monolinguals when adjusting for severity of cognitive impairment . The latter did not only comprise Brodmann areas relevant to speech and language but also structures typically involved in AD pathology such as the temporal and the parietal cortices.